World finance and economic stability : selected essays of James Tobin - Tobin, James (Cheltenham, UK ; Northampton, MA, USA : Edward Elgar, 2003)
Nobel Prize winner James Tobin has made outstanding contributions to modern macroeconomics. In this final collection of his work he examines the economics and policies of the United States and its relations with other major economies after 1990.
Includes bibliographical references and index.
rpm 26/08/16
Loans
Keywords: Finance; Monetary policy; International finance; Fiscal policy; Economic policy; United States